Fins & Scales: An Introduction to Bony Fish—A Marine Science Project Guide for 4-H Leaders and Educators - Karen Blyler (EDIS)
The Fins and Scales Project is intended for youth age 11-13 (Intermediate 4-Hers). The Leaders Guide follows the layout of the Youth Project Book and provides a suggested approach for each section. Each section of the Leaders Guide contains: Additional background information, answer key, additional activities, opportunities to review, “dive deeper,” and “think like a scientist.” This 52-page project guide was written by Karen Blyler, and published by the UF Department of 4-H Youth Development, October 2014.